Impact of oxidation processes on the composition and biodegradability of soluble organic nutrients in wastewater effluents. (30th July 2020) - Tooker, Nicholas B.; Gao, Ce; Onnis‐Hayden, Annalisa; Gu, April Z.
Abstract: The characteristics and bioavailability of wastewater derived organic nutrients and their susceptibility to removal technologies have implications in nutrient loading to aquatic environments and their contributions to eutrophication. Therefore, a better understanding of treatability of effluent organic nutrients is of interest for water resource recovery facilities (WRRFs) and regulators. Oxidation processes (OPs) can reduce concentrations of soluble organic nutrients and convert them into more biodegradable forms. In this study, three WRRF effluents were treated with low‐pressure ultraviolet (UV) irradiation, hydrogen peroxide (H2 O2 ), and combined UV/H2 O2 . Untreated and treated effluents were subjected to nitrogen and phosphorus speciation analyses and soluble organic nitrogen (SON) biodegradability assays. The OP treatments did not change SON concentrations significantly. For two WRRFs, OP treatments decreased soluble organic phosphorus (SOP) and seemed to convert it into soluble acid hydrolyzable phosphorus (SAHP), indicating possible increases in phosphorus bioavailability. Fingerprinting and quantification of dissolved organic matter (DOM) using fluorescence spectroscopy with parallel factor analysis revealed changes in DOM pool composition in response to OPs treatments, which suggests likely organic nutrients composition changes. Based on biodegradability assessments, OP treatments likely changed the composition and biodegradability of effluent SON compounds. Combined UV/H2 O2 treatment seemed more effective than other OPs at oxidizing some of the organic nutrients. Practitioner points: Treatment of secondary or tertiary effluent with UV, H2 O2, or UV/ H2 O2 was generally not effective at mineralizing SON and SOP, when applied at the doses used in this study. Treatment resulted in observable changes in DOM compositions, likely including SON and SOP compounds. Combined UV/H2 O2 treatment was more effective than UV or H2 O2 alone at oxidizing some DOM compounds. The BSON (bioavailable SON) assay indicated that the composition of the SON pool in the effluents was likely changed by the OP treatments. This was supported by fluorescence spectroscopy analysis. Abstract : UV, H2 O2, and combined UV/H2 O2 oxidation processes converted soluble organic nitrogen and soluble organic phosphorus compounds in secondary effluent into more biodegradable forms.